Cover Image, Volume 38, Number 5, June 2019. Issue 5 (18th June 2019) - Chelimsky, Gisela G.; Yang, Sheng; Sanses, Tatiana; Tatsuoka, Curtis; Buffington, C. A. Tony; Janata, Jeffrey; McCabe, Patrick; Dombroski, Mary‐Alice; Ialacci, Sarah; Hijaz, Adonis; Mahajan, Sangeeta; Zolnoun, Denniz; et al.
Abstract : The Front Cover : The cover image, by Gisela G. Chelimsky et al., is based on the Original Clinical Article Autonomic neurophysiologic implications of disorders comorbid with bladder pain syndrome vs myofascial pelvic pain . DOI: 10.1002/nau.23995 . Cover Credit: Cover image ©Thomas Chelimsky images and Nightowl images